Zmiany strukturalne – zjawisko i jego pomiar - Onufer, Aneta (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The main goal of the article is to present the concept of structural change and possible ways to measure it. For the purposes of this paper, structural change refers to changes in a commodity structure. The article underlines the problem of choosing the right indicators which may be used for an analysis of the structure of the economy and its changes. The indicators may be classified into one of three categories: indicators characterizing the structure of the economy, comparing economic structures (or, in other words, measuring the similarity of two or more structures) and measuring the speed of structural changes. The other problems which are mentioned in the paper are choosing the right system of prices and data classification which give a base for statistical analysis of the structural changes.
Keywords: zmiany strukturalne; gospodarka; wskaźniki ekonomiczne